Modelling an axisymmetric perforated brick catalyst - Mat Yamin, Ahmad Kamal (2010)
The use of perforated bricks for automotive exhaust catalysts offers the prospect of reducing emissions by providing a more uniform flow within the reactor due to internal mixing. Modelling the flow distribution for these structures using the "porous medium" approach requires knowledge of both axial and transverse brick resistance. The former were measured by presenting uniform flow to the front face of the brick. The transverse resistance was deduced by best matching CFD predictions to measurements of the radial flow profiles obtained downstream of the brick when presented with non-uniform flow at its front face